Kinetic Monte Carlo simulation of Pt discontinuous thin film formation adsorbed on Au - Rojas, Mariana Isabel (2005)
The evolution of a non-uniform Pt film adsorbed on Au, in contact with a solution containing [PtCl6]2- ions was studied by means of lattice gas/kinetic Monte Carlo simulations with pair potentials at 300 K in the canonical ensemble. We found that the evolution of the morphology takes place through two types of exchange: surface diffusion and diffusion mediated by the solution, which occur with different probabilities or rates. These two types of moves were included in the simulation. By means of this dynamic description, it was possible to estimate the exchange rate of Pt atoms on a Au flat surface. A linear dependence was found between the exchange rate and the reciprocal of the number of particles. This function was used to extrapolate the exchange rate to a system of macroscopic size. The standard exchange current density calculated from this value was 5.24 x10-6 A cm2. he morphological evolution of the filmas a function of the time was also studied.